PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENDORONG BUDAYA PEMBELAJARAN UNTUK MENINGKATKAN RESKILLING DAN UPSKILLING - Anrifa Izatul Ilmi; Krisdayanti Krisdayanti; Tiana Setianingrum (Cahaya Ilmu Bangsa, 2025)
Transformational leadership plays a crucial role in shaping an adaptive and skill-oriented learning culture in the workplace. In the context of rapid technological changes and dynamic market demands, the need for employee reskilling and upskilling has become increasingly urgent for organizations. This article explores how leaders with a transformational style can inspire employees to continuously learn and enhance their skills, using approaches that foster motivation, innovation, and a deep understanding of the importance of personal development. Through case studies and literature review, the article analyzes the positive impact of a learning culture in driving reskilling and upskilling, as well as identifies potential challenges faced by organizations. The findings suggest that transformational leadership is effective in promoting continuous learning, ultimately enhancing organizational competitiveness and resilience.